Utilizing virtual Singapore platform to quantify benefits of autonomous vehicles - Mehta, Priyanka (2021)
This studydiscusseson methods of measuring Autonomous Vehicles’ benefitsin the urban city of Singapore. The study has exploitedAV modelling and simulation techniques in Virtual environment. The team has made use of AV simulation software in conjunction with traffic simulation and architecture design software. The AV simulation software providesthe capability ofdeployingdifferent sensors such as virtual LIDARwith physics based rendering, vision sensors, Inertial Measurement Unit (IMU) etc. These sensor measurements help the vehiclesto interpretsurrounding environment used for localization, perception, path planningetc. For a realistic environment, we have integrated thesimulation software with a real-time traffic simulator. Thistraffic simulator is able topopulate vehicles based on real-traffic conditions. The real traffic data is collected with help of our research collaborator, Land Transport Authority (LTA),Singapore. The integration of traffic dataand simulator togetherhelps to test and analyse different use cases to quantify the benefits like area saving, transit time etc.and express the challenges involved in adaptingSingapore to an AV environment. This paper presents a perspective of utilizing Virtual Singapore platform for testing and validating AV deployment in Singapore road network through a combined interface of different software.